Sequencing intact membrane proteins using MALDI mass spectrometry - Zhamungui Sánchez, Edison; Hijazi, Hassan; Haidar, Jana; Mecarelli, Enrica; Bauda, Elda; Petit-Härtlein, Isabelle; Teulon, Jean-Marie; Pellequer, Jean-Luc; Boeri Erba, Elisabetta (Frontiers in Analytical Science, 2023)
Membrane proteins are key players in many cellular events and they represent crucial drug targets. Matrix Assisted Laser Desorption Ionization mass spectrometry (MALDI MS) is a valuable approach to investigate them. To our knowledge, there are only a few reports of sequencing small membrane proteins using MALDI in source decay (ISD). We report the successful fragmentation and sequencing of membrane proteins up to 46 kDa by MALDI ISD. We have (i) investigated key MALDI parameters, which influence the sequencing of a soluble protein; (ii) used atomic force microscopy to observe our samples and correlate their topological features with MALDI data, allowing us to optimize fragmentation conditions. (iii) We have sequenced N-and C-termini of three membrane proteins (SpoIIIAF, TIM23, and NOX), solubilized in three different ways. Our results indicate that type of detergent and buffer are of key importance for a successful MALDI ISD sequencing. Our findings are significant since sequencing membrane proteins enables unique characterization of challenging biomolecules. The resulting fragmentation patterns provide key insights into the identity of proteins, their sequences, modifications and other crucial information, such as the position of unexpected truncation.